Impact of the Utilization of Artificial Intelligence in the Development of Electrical Engineering - K. Daqrouq; S. Alghamedi; S. Alwaseli; A. F. Alkhateeb; Sami Alghamdi; M. N. Ajour; A. S. Balamash; A. Milyani; K. Alharbi; A. M. Rushdi (Journal of Engineering)
A study to examine past research about artificial intelligence (AI) technology applications within electrical engineering (EE) systems is presented. EE stands out as one of the areas where research into AI acquires the most substantial increase in attention. This study explores AI transformation possibilities for EE because of modern technology progress and the critical need for field innovations. Recent research papers obtained from open literature form the survey dataset to create a complete understanding of AI deployment across EE major areas. Particularly, renewable energy (RE), power systems, control systems, and power electronics domains are studied. The research results showcase the advantages and difficulties that AI implementation produces in these individual EE domains. A research review of the main AI methods includes both their effective use cases and potential research paths for future work. This research seeks to provide academic directions for scholars who want to use AI in EE by explaining current approaches as well as inspiring further innovation in this continuously progressing field.